2023
DOI: 10.1002/ep.14191
|View full text |Cite
|
Sign up to set email alerts
|

A review on microbial fuel cell technology for Brewery industry wastewater treatment – From fundamentals to pilot scale studies

Abstract: Industries play an important role in the economic growth of any nation, whereas they release pollutants, which impact our environment seriously. Owing to the rapid climate change and global warming, our earth is searching for different sustainable energy technologies. Microbial fuel cell technology is emerging as one of the most versatile sustainable energy technology, with their ability to tap the energy stored in the wastewater and convert it directly into electrical energy. Though MFC research is still in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 112 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…One of the main research focus has been the development of microbial fuel cells (MFCs) that harness electrical current from waste both in liquid and in solid form . For example, pilot-scale studies have shown microbial fuel cells to be commercially feasible for sustainable brewery wastewater decontamination . In addition, using the novel halophile Salinivibrio sp.…”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%
“…One of the main research focus has been the development of microbial fuel cells (MFCs) that harness electrical current from waste both in liquid and in solid form . For example, pilot-scale studies have shown microbial fuel cells to be commercially feasible for sustainable brewery wastewater decontamination . In addition, using the novel halophile Salinivibrio sp.…”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%